Validation of a Ramp Running Protocol for Determination of the True VO2max in Mice - Ayachi, Mohamed; Niel, Romain; Momken, Iman; Billat, Véronique L.; Mille-Hamard, Laurence (Frontiers in Physiology, 2016)
In the field of comparative physiology, it remains to be established whether the concept of VO2max is valid in the mouse and, if so, how this value can be accurately determined. In humans, VO2max is generally considered to correspond to the plateau observed when VO2 no longer rises with an increase in workload. In contrast, the concept of VO2peak tends to be used in murine studies. The objectives of the present study were to determine whether (i) a continuous ramp protocol yielded a higher VO2peak than a stepwise, incremental protocol, and (ii) the VO2peak measured in the ramp protocol corresponded to VO2max. The three protocols (based on intensity-controlled treadmill running until exhaustion with eight female FVB/N mice) were performed in random order: (a) an incremental protocol that begins at 10 m.min-1 speed and increases by 3 m.min-1 every 3 min. (b) a ramp protocol with slow acceleration (3 m.min-2), and (c) a ramp protocol with fast acceleration (12 m.min-2). Each protocol was performed with two slopes (0° and 25°). Hence, each mouse performed six exercise tests. We found that the value of VO2peak was protocol-dependent (p<0.05) and was highest (59.0 ml.kg 0.75.min-1) for the 3 m.min-2 0° ramp protocol. In the latter, the presence of a VO2max plateau was associated with the fulfilment of two secondary criteria (a blood lactate concentration > 8 mmol.l-1 and a respiratory exchange ratio >1). The total duration of the 3 m.min-2 0° ramp protocol was shorter than that of the incremental protocol. Taken as a whole, our results suggest that VO2max in the mouse is best determined by applying a ramp exercise protocol with slow acceleration and no treadmill slope.